Explaining regional variation in equilibrium real estate prices and income - Oliver Bischoff (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2010)
We combine the real estate model of Potepan (1996) with the spatial equilibrium approach of Roback (1982) to prove the interdependency of housing prices, rental prices, building land prices and income via one simultaneous equilibrium analysis. Using unique cross-sectional data on the majority of German counties and cities for 2005, we estimate the equations in their structural and reduced form. The results show significantly positive interaction effects of income and real estate prices. Moreover, we can confirm model predictions concerning the majority of exogenous determinants. In particular, expectations about population development seem to be among the most important determinants of price and income disparities between regions in the long term.
Keywords: C2; C31; R11; R13; R21; R31; 330; Regional Housing Markets; Spatial Equilibrium Analysis; Simultaneous Equation; Germany